Study of the initial magnetic permeability of LiTiZnMn ferrites obtained by liquid-phase sintering under radiation-thermal and thermal conditions; Eurasian Physical Technical Journal; Vol. 19, No. 1 - Surzhikov A. P. Anatoly Petrovich (2022, 2022)
Title screen